Armies and Ecosystems in Premodern Europe : The Meuse Region, 1250-1850. - Govaerts, Sander. (War and Conflict in Premodern Societies Series, 2021)
A multi-faceted and original study of the complex interactions between armies and their ecosystems, taking a long view of current debates about the environmental impact of the military.